MEASURING EFFECTIVENESS OF ISLAMIC STUDIES DISTANCE EDUCATION IN THE DIGITAL ERA AT THE INTERNATIONAL OPEN UNIVERSITY (IOU) INDONESIA - Hartono, Haryani Santo (Al-Iqro', 2024)
International Open University (IOU) is an international accredited campus that created new breakthrough by offering the concept of distance education since its inception. IOU is a pioneer in implementing distance learning with a concentration on Islamic Studies through digital media. Entering Indonesia as the country with the largest Muslim population, IOU opened a special Indonesian language program. This study is a form of Measures of Effectiveness (MOE) of Islamic Studies distance education through digitalization at the IOU Indonesia. The method used in this research is descriptive qualitative. The data collection techniques used were observations, interviews, and literature review. The results of the study concluded that IOU Indonesia in some cases has its own independent program, but in general it is based on the central that has all the components of distance education through digitalization except for controls for students or graduates. IOU Indonesia also fulfills the basic principles of learning Islamic Studies.